Disaster Management Capabilities in Zimbabwe: The Context of Africa Agenda 2063 - Chikowore, Godfrey; Nhavira, John David; Mashonganyika, Terence Motida; Munhande, Constantine (Springer, 2022)
Historically, disasters have adversely affected nations across the world, inflicting wide ranging losses on one hand while on the other hand creating development opportunities for urban communities. Recovery instruments and transformative efforts by Zimbabwe and international stakeholders in disaster management assumed the form of conventions on climate change and other means commonly agreed at international level that were destined to address perceived humanitarian crisis (Hyogo and Sendai Disaster Frameworks, 2015–2030). Yet, even as disaster presupposes a disruptive situation it equally provokes an attitude of restoration as Zimbabwe reclaims its position in a heavily contested world. Recovery should take the form of industrialisation or infrastructure rehabilitation where economies have been disrupted as Zimbabwe; among nations, makes frantic efforts to align with global development trends. In the light of preceding conversation, this chapter seeks to explore disaster management capabilities of Zimbabwe evaluating hazards and opportunities characteristic of disaster recovery phases in a context of opportunities availed by development cooperation programmes as Africa Agenda 2063. Informed by the theory of disaster management and transformation, the work is founded on a descriptive research design augmented by quantitative and qualitative data analysis and comparative data analysis. In conclusion, the study recommends cooperation in disaster management as a strategy for minimisation of losses on one hand and uplifting the affected urban settlements to ranks of modern global cities as afforded by robust industrialisation programmes grounded in development cooperation frameworks.